Is the Living Body the Last Thing Left Alive? The New Performance Turn, Its Histories and Its Institutions. - Costinas, Cosmin; Lopèz, Miguel; Bishop, Claire; Buden, Boris; Cheng, Amy; Flores, patrick; Edwards, Adrienne; Guerrero, Inti; Janevski, Ana; Lepecki, André; Yinghua Lu, Carol; Noack, Ruth; et al. (Berlin : Sternberg Press, 2017)
Cvejic, Bojana ; Gill, Gauri ; Gill, Simryn ; Ishida, Tetsuya ; Lai, Firenze ; Le Roy, Xavier ; Lomasko, Victoria ; Mroué, Rabih ; Pelmus, Manuel ; Roysdon, Emily ; Spanberg, Marten ; Yangjiang Group ; Belkin, Ayon
Performance, Queer art, dance
Is The Living Body the Last Thing Left Alive? Conference, Para Site International, Hongkong, 2014
boek